THE CONCEPT OF MULTIMORBIDITY IN RHEUMATOLOGIC PRACTICE - A. V. Gordeev; E. A. Galushko; E. L. Nasonov (Научно-практическая ревматология)
The undoubted and legitimate interest of investigators in comorbidities in rheumatic diseases has not faded in the past decade; however, the concept of multimorbidity has not yet been integrated into either clinical practice or rheumatology researches. The terms comorbidity and multimorbidity are frequently and not always consciously used as interchangeable, which leads to some confusion in their terminology and accordingly in the development of further research strategies. The concepts of concurrent pathology and multimorbidity are not mutually exclusive or contradictory to each other, but they should be considered from another point of view than comorbidity. The problem of multimorbidity disease is a rule rather than an exception to clinicians who are engaged in the treatment of mainly typical patients with rheumatic diseases. Recent researches could outline few key areas to further study the conception of multimorbidity in rheumatology practice, which would be able to turn international rheumatology research community from rheumatic disease to the patient as a whole.